ALTERNATIVE METHODOLOGICAL APPROACHES FOR THE INVESTIGATION OF CONCEPTUAL ANAPHORA - Mahayana C. GODOY; Edson FRANÇOZO; Angélica FERREIRA (Signum: Estudos da Linguagem, 2013)
This paper intends to study the processes involved in resolving plural and singular pronouns when their antecedent is a collective (e.g., “the team”). Our main goal in choosing a topic that has been vastly studied (e.g., OAKHILL et al., 2012; FARIA; LEITÃO; FERRARI-NETO, 2012) was to find a methodological approach to explain the different results reported by previous research. Besides that, we aim at comprehending the semantic characteristics of collectives that can influence pronominal resolution, an issue consistently neglected by previous studies. Considering these goals, we developed an eye-tracking experiment in which we compared: (a) the processing of plural and singular pronouns; (b) the influence institutional and distributive predicates exert over pronominal resolution. Our findings are supported by previous data (CARREIRAS; GERNSBACHER, 1992; OAKHILL et al., 1992), indicating that, in general, plural pronouns are easier to process compared to singular ones. Furthermore, our conclusion points out to the fact that the type of predication attributed to a collective term can attenuate or strengthen the difference in cognitive cost involved in processing plural and singular pronouns.